Experimental study on rheological properties of serrate discontinuity under stepwise loading - Guang-hui Tian; Bao-qing Mei; Qing-zhao Zhang; Yu-xi Hao; Yan-zhi Zhu; Yong-zhi Jiu (Scientific Reports)
Abstract Serrate discontinuity creep and stress relaxation tests are conducted to analyze the differences and relationships between creep, relaxation, and long-term strength using the same normal stress and shear stress levels. Both the creep and relaxation curves may be classified into two different phases: decelerating and steady. However, the trend of the creep curve is opposite to that of the stress relaxation curve. Additionally, we observed that the maximum creep displacement and maximum relaxation stress increase as the slope angle increases. The energy changing properties of rocks during creep and relaxation processes are unequal, as indicated by experiment results, indicating that creep and relaxation are not equal. An empirical model has been developed for the maximal relaxation stress and the shear stress level, which provides a better fit to the experimental data. Based on the same mechanism, the long-term strength determined by the creep test and the relaxation test shows little difference and is both close to the yield strength of the stress-displacement curves during the creep and relaxation processes, respectively. This study can provide a deeper understanding of the time-dependent characteristics of discontinuities by integrating creep, relaxation, and long-term strength.